2014
DOI: 10.1177/0194599814542587
|View full text |Cite
|
Sign up to set email alerts
|

Untreated Head and Neck Surgical Disease in Sierra Leone: A Cross‐sectional, Countrywide Survey

Abstract: These results show limited access for patients to be evaluated for a potential H&N surgical condition in Sierra Leone. The true incidence of untreated surgical disease is unknown as most respondents were not evaluated by a surgeon. This survey could be used in other countries as health care professionals assess surgical needs throughout the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…This relationship between children with hearing loss and worse educational outcomes has also been associated with minimal or unilateral hearing loss ( Bess et al, 1998 ; Lieu et al, 2010 ; Lieu, 2012 ). Survey data from Sierra Leone have indicated that financial constraints are a major deterrent for seeking care for diseases affecting the head and neck ( Van Buren et al, 2014 ). However, treatment of hearing loss through the use of hearing aids or cochlear implants has been shown to be both cost-effective and mitigate these long-term deficits ( Tsakiropoulou et al, 2007 ; Baltussen and Smith, 2009 ; Baltussen et al, 2009 ; Tomblin et al, 2014 ; Dawes et al, 2015 ; Magro et al, 2018 ; Vo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This relationship between children with hearing loss and worse educational outcomes has also been associated with minimal or unilateral hearing loss ( Bess et al, 1998 ; Lieu et al, 2010 ; Lieu, 2012 ). Survey data from Sierra Leone have indicated that financial constraints are a major deterrent for seeking care for diseases affecting the head and neck ( Van Buren et al, 2014 ). However, treatment of hearing loss through the use of hearing aids or cochlear implants has been shown to be both cost-effective and mitigate these long-term deficits ( Tsakiropoulou et al, 2007 ; Baltussen and Smith, 2009 ; Baltussen et al, 2009 ; Tomblin et al, 2014 ; Dawes et al, 2015 ; Magro et al, 2018 ; Vo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This calls into question the accuracy of previously performed community-based surveys of surgical conditions that used nonvalidated survey tools and similar sampling methods. [15][16][17][18][19][20] To improve measurement of unmet surgical disease epidemiology, future studies should consider a few implementation options. Assessment can be grounded on community-based clinical examination, although this is resource and time intensive.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Recent studies reported results from a population-based survey tool attempting to collect data on a broad spectrum of potentially untreated surgical disease. [15][16][17][18][19][20] However, to our knowledge, this tool remains unvalidated. Without validation, it is unknown if survey results are sufficiently accurate for policy planning.…”
mentioning
confidence: 99%
“…Untreated surgical conditions could contribute to 20% of the deaths affecting young adults in LMICs and to about 10% of all deaths globally [2,3]. Studies from several sub-Saharan African countries have found a prevalence of 6 to 35% for conditions needing surgical consultation or treatment [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…About 90% of these take place in low-and middle-income countries (LMICs) [4]. Deaths and morbidity from surgery-related diseases in LMICs can be reduced by scaling up basic, life-saving surgical care [6,7].…”
Section: Introductionmentioning
confidence: 99%